2005
DOI: 10.1002/gene.20112
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency somatic mutagenesis in smooth muscle cells and cardiac myocytes in SM22?-Cre transgenic mice

Abstract: The cytoskeletal protein SM22alpha is expressed in visceral and vascular smooth muscle cells (SMCs), in cardiac myocytes, and in the myotomal components of the somites during murine embryonic development. In this report, we describe the generation and characterization of transgenic mice expressing Cre-recombinase under the transcriptional control of the -2.8-kb SM22alpha promoter. Following interbreeding with the R26R reporter strain, Cre-dependent beta-galactosidase expression was observed as early as embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
132
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(138 citation statements)
references
References 15 publications
6
132
0
Order By: Relevance
“…On Western blot analysis of GR protein from hearts of control and Sm-22 Creϩ GR loxP/loxP mouse pairs, we found that, if anything, heart GR was slightly increased and certainly not decreased in Sm-22 Creϩ GR loxP/loxP mice ( Figure 4B), suggesting that there was no significant GR deletion from cardiac myocytes in our KO mice. Consistent with this and previous studies, 15,16 we found no differences in heart rate between the two groups either before or after DEX administration ( Figure 5). Our data suggest a critical role of VSM GR on the acute hypertensive response to GC.…”
Section: No Apparent Role For Vsm Gr In Basal Bp Regulationsupporting
confidence: 93%
See 1 more Smart Citation
“…On Western blot analysis of GR protein from hearts of control and Sm-22 Creϩ GR loxP/loxP mouse pairs, we found that, if anything, heart GR was slightly increased and certainly not decreased in Sm-22 Creϩ GR loxP/loxP mice ( Figure 4B), suggesting that there was no significant GR deletion from cardiac myocytes in our KO mice. Consistent with this and previous studies, 15,16 we found no differences in heart rate between the two groups either before or after DEX administration ( Figure 5). Our data suggest a critical role of VSM GR on the acute hypertensive response to GC.…”
Section: No Apparent Role For Vsm Gr In Basal Bp Regulationsupporting
confidence: 93%
“…BP measured at 14 d showed that Sm-22 Creϩ GR loxP/loxP mice maintained a MAP of 121.0 Ϯ 5.3 mmHg and controls maintained a MAP of 119.2 Ϯ 3.1 mmHg (P ϭ 0.36), suggesting that Sm-22 Creϩ GR loxP/loxP mice likely attain the same rise in BP observed in the controls with continued DEX therapy. Previous studies that have used Sm-22 Cre in the generation of transgenic mice have suggested that Sm-22 Cre is expressed at high levels in murine cardiac muscle 15 ; however, in the Sm-22 Cre model we used, only minimal cardiac expression was observed. 13 To determine whether GC effects on cardiac muscle could underlie the BP phenotype we observed in our model, we assessed GR staining in the cardiac muscle of Sm-22 Creϩ GR loxP/loxP and control mice and found no significant difference between Creϩ and CreϪ littermates ( Figure 4A).…”
Section: No Apparent Role For Vsm Gr In Basal Bp Regulationmentioning
confidence: 84%
“…This report shows for the first time that the cytoskeletal protein transgelin [65] exists in longterm stimulated skeletal muscles. Transgelin, also referred to as SM22a [66], has been localized to vascular smooth muscle cells throughout the arterial and venous system. It has been described in visceral smooth muscle cells in various organs and the heart, but as being absent from mature skeletal muscle [66].…”
Section: Discussionmentioning
confidence: 99%
“…Transgelin, also referred to as SM22a [66], has been localized to vascular smooth muscle cells throughout the arterial and venous system. It has been described in visceral smooth muscle cells in various organs and the heart, but as being absent from mature skeletal muscle [66]. The electrostimulation-dependent induction revealed by DIGE analysis suggests transgelin as another excellent biomarker of fast-to-slow fibre transition.…”
Section: Discussionmentioning
confidence: 99%
“…This phenotypic variation in 2 different promoters likely relates to the activation time and the strength of each promoter. Indeed, SM22α-Cre is activated earlier at E9.5 16,27 than Myh11-Cre at E13.5. 28 SM22α (Tagln) is expressed higher than Myh11 in jejunal and colon SMCs.…”
Section: Serum Response Factor Knockout Phenotypementioning
confidence: 95%